KENABIAN SEBAGAI TINDAKAN POLITIK - Asri, Syamsul (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2017)
Prophethood (nubuwwah) is an implementation of the authority of divine lordship (to order and to protect) in a so-called divine city in which justice (‘adalah) as the fundamental objective of divine laws and politics may be rigidly enforced within the milieu of socio-politics. The purpose of this prophetic political engagement is to restore the ritual formal principles (i’tibari) of the sharia to its realistic fundamental principles (takwini) so that the Truth (al–Haq) may be flawlessly observed to its utmost level of possibilities.